Preventive but Not Curative Efficacy of Celecoxib on Bladder Carcinogenesis in a Rat Model - José Sereno; Belmiro Parada; Flávio Reis; Fernanda X. Cunha; Edite Teixeira-Lemos; Patrícia Garrido; Rui Pinto; Petronila Rocha-Pereira; Paula Neto; José Ruivo; Paulo Rodrigues-Santos; Sara Nunes; et al. (Mediators of Inflammation)
To evaluate the effect of a cyclooxygenase 2 inhibitor, celecoxib (CEL), on bladder cancer inhibition in a rat model, when used as preventive versus as curative treatment. The study comprised 52 male Wistar rats, divided in 5 groups, during a 20-week protocol: control: vehicle, carcinogen: 0.05% of N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN), CEL: 10 mg/kg/day of the selective COX-2 inhibitor Celebrex, preventive CEL (CEL+BBN-P), and curative CEL (BBN+CEL-C) groups. Although tumor growth was markedly inhibited by the preventive application of CEL, it was even aggravated by the curative treatment. The incidence of gross bladder carcinoma was: control 0/8(0%), BBN 13/20(65%), CEL 0/8(0%), CEL+BBN-P 1/8(12.5%), and BBN+CEL-C 6/8(75%). The number and volume of carcinomas were significantly lower in the CEL+BBN-P versus BBN, accompanied by an ample reduction in hyperplasia, dysplasia, and papillary tumors as well as COX-2 immunostaining. In spite of the reduction of tumor volumes in the curative BBN+CEL-C group, tumor malignancy was augmented. An anti-inflammatory and antioxidant profile was encountered only in the group under preventive treatment. In conclusion, preventive, but not curative, celecoxib treatment promoted a striking inhibitory effect on bladder cancer development, reinforcing the potential role of chemopreventive strategies based on cyclooxygenase 2 inhibition.